Clinical, epidemiological and laboratory aspects of patients with American cutaneous leishmaniasis in the State of Pernambuco Aspectos clínicos, epidemiológicos e laboratoriais de pacientes com leishmaniose cutânea americana no Estado de Pernambuco - Luiza de Campos Reis; Maria Edileuza Felinto de Brito; Éricka Lima de Almeida; Simone Marta Félix; Ângela Cristina Rapela Medeiros; Cláudio Júlio Silva; Valéria Rêgo Alves Pereira (Revista da Sociedade Brasileira de Medicina Tropical, 2008)
The diagnosis for American cutaneous leishmaniasis is based on an association of clinical, epidemiological and laboratory characteristics. The present study identified the circulating species of Leishmania in the State of Pernambuco, described its clinical-epidemiological characteristics and diagnosed the disease. Nineteen patients presenting active lesions who had been diagnosed through clinical evaluation and laboratory tests were selected. The tests included direct investigation, in vitro culturing, Montenegro skin test, indirect immunofluorescence and polymerase chain reaction. The Montenegro Skin Test showed positive results in 89% of the patients; indirect immunofluorescence, in 79%; direct investigation, in 58%; and polymerase chain reaction in 75%. Seven Leishmania (Viannia) braziliensis samples were isolated from these patients and were characterized by means of specific monoclonal antibodies. These data confirm that a combination of different diagnosis techniques is needed in order to obtain efficient results and that, so far, Leishmania (Viannia) braziliensis is the only species responsible for American cutaneous leishmaniasis infection in Pernambuco. Thus, it is essential to identify the parasite species involved in cases of human disease in an endemic area in order to determine the clinical and epidemiological characteristics, especially with regard to diagnosis, therapy development and disease prognosis. O diagnóstico da leishmaniose cutânea americana é baseado na associação dos aspectos clínicos, epidemiológicos e laboratoriais. O presente estudo identificou a espécie de Leishmania circulante no Estado de Pernambuco, descreveu os aspectos clínico-epidemiológicos e diagnosticou a doença. Foram selecionados 19 pacientes apresentando lesão ativa e diagnosticados através de avaliação clínica e pelos exames laboratoriais que incluíram a pesquisa direta, cultivo in vitro, intradermorreação de Montenegro, imunofluorescência indireta e reação em cadeia de polymerase. A intradermorreação de Montenegro ...